Kak zhit' budem? . Kak zhit' budem? . How Will We Live? . Как жить будем? - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Discussion of the prospects of keeping civil peace and consent in Russia. Featured in the program: Abdulatipov, Ramazan Gadzhimuradovich (Deputy Head of the Federation Council); Kubarev, Eduard Alekseevich (Chairman of the Supreme Soviet of Chuvashia); Stepanov, Viktor Nikolaevich (Chairman of the Supreme Soviet of the Republic of Kareliia) Contributors: Lapina, Irina (Anchor) Дискуссия о перспективах поддержания гражданского мира и согласия в России. В программе участвуют: Абдулатипов, Рамазан Гаджимурадович (Заместитель председателя Совета Федерации); Кубарев, Эдуард Алексеевич (Председатель Верховного Совета Чувашии); Степанов, Виктор Николаевич (Председатель Верховного Совета Республики Карелии) Создатели: Лапина, Ирина (Ведущий/Ведущая)